Long-term Tillage and Nitrogen Fertilization Effects on Soil Properties and Crop Yields - Muhajir Utomo; Irwan Sukri Banuwa; Henrie Buchari; Yunita Anggraini; . Berthiria (JOURNAL OF TROPICAL SOILS, 2013)
The impact of agricultural intensification on soil degradation now is occurring in tropical countries. The objective of this study was to determine the effect of long-term tillage and N fertilization on soil properties and crop yields in corn-soybean rotation. This long-term study which initiated since 1987 was carried out on a Typic Fragiudult soil at Politeknik Negeri Lampung, Sumatra (105o13’45.5"-105o13’48.0"E, 05o21’19.6"-05o21’19.7"S) in 2010 and 2011. A factorial experiment was arranged in a randomized block design with four replications. The first factor was tillage system namely intensive tillage (IT) and conservation tillage (CT) which consist of minimum tillage (MT) and no-tillage (NT); while the second factor was N fertilization with rates of 0, 100 and 200 kg N ha-1 applied for corn, and 0, 25, and 50 kg N ha-1 for soybean. The results showed that  bulk density and soil strength at upper layer after 24 years of cropping were similar among treatments, but the soil strength under IT at 50-60 cm depth was 28.2% higher (p<0.05) than NT. Soil moisture and temperature under CT at 0-5 cm depth were respectively 38.1% and 4.5%  higher (p<0.05) than IT. High N rate decreased soil pH at 0-20 cm depth as much as 10%,  but increased total soil N at 0-5 cm depth as much as 19% (p<0.05).  At 0-10 cm depth, MT with no N had highest exchangeable K, while IT with medium N rate had the lowest (p<0.05). At 0-5 cm depth, MT with no N had highest exchangeable Ca, but it had the lowest (p<0.05) if combined with higher N rate. Microbial biomass C throughout   the growing season for NT was consistently highest and it was 14.4% higher (p<0.05) than IT. Compared to IT, Ap horizon of CT after 24 years of cropping was deeper, with larger soil structure and more abundance macro pores. Soybean and corn yields for long-term CT were 64.3% and 31.8% higher (p<0.05) than IT, respectively. Corn yield for long-term N with rate of 100 kg N ha-1 was 36.4% higher (p<0.05) than with no N.Keywords: Conservation tillage, crop yields, N fertilization, soil properties[How to Cite: Utomo M, IS Banuwa, H Buchari, Y Anggraini  and  Berthiria. 2013.Long-term Tillage and Nitrogen Fertilization Effects on Soil Properties and Crop Yields. J Trop Soils 18 (2): 131-139. Doi: 10.5400/jts.2013.18.2.131][Permalink/DOI: www.dx.doi.org/10.5400/jts.2013.18.2.131] REFERENCESAl-Kaisi and X Yin. 2005. Tillage and crop residue effects on soil carbon dioxide emission in corn-   soybean rotation. J Environ Qual 34: 437-445. Pub Med. Barak P, BO Jobe, AR Krueger, LA Peterson and DA Laird. 1997. Effects of long-term soilacidification due to nitrogen inputs in Wisconsin. Plant Soil 197: 61-69.Blake GR and KH  Hartge. 1986.  Bulk density. In: A Klute (ed). Methods of Soil Analysis. ASA and SSSA.  Madison, Wisconsin, USA, pp. 363-375.Blanco-Canqui H and R Lal. 2008. No-till and soil-profile carbon sequestration: an on farm assessment. Soil Sci Soc Am J  72: 693-701.  Blanco-Canqui H, LR  Stone and PW Stahlman.  2010. Soil response to long-term cropping systems on an Argiustoll in the Central Great Plains. Soil Sci Soc Am J 74: 602-611.Blevins RL, MS Smith, GW Thomas and WW Frye. 1983. Influence of conservation tillage on soil properties.  J Soil Water Conserv 38: 301-305.Blevins RL, GW Thomas and PL Cornelius. 1977 Influence of no-tillage and nitrogen  fertilization on certain soil properties after 5 years of continuous corn. Agron J 69: 383-386.Blevins, RL and WF Frye, 1993. Conservation tillage: an ecological approach to soil management. Adv Agron 51: 34-77.Brady NC and RR Weil. 2008. The nature and properties of soils. Pearson Prentice Hall. Fourteenth Edition. New Jersey, 965 p.Brito-Vega, H, D Espinosa-Victoria, C Fragoso, D Mendoza, N De la Cruz Landaro and A Aldares-Chavez. 2009. Soil organic particle and presence of earthworm under different tillage systems. J Biol Sci  9: 180-183.Derpch, R 1998. Historical review of no-tilage cultivation of crops. JIRCAS Working Rep. JAPAN Int  Res Ctr for Agric Sciences, Ibaraki, Japan 13: 1-18.  Diaz-Zorita, M., JH Grove, L Murdock, J Herbeck and E Perfect. 2004. Soil structural disturbance effects on crop yields and soil properties in a no-till production system. Agron J 96: 1651-1659.Dickey EC, PJ Jasa and RD Grisso. 1994. Long-term tillage effect on grain yield and soil properties in a soybean/grain sorghum Rotation. J Prod Agric 7: 465 - 470.Edwards WM, LD, Norton, CE, Redmond. 1988. Characterizing macro pores that affect infiltration into non tilled soil. Soil Sci  Soc  Am  J 52: 483-487.Fernandez RO, PG Fernandez, JVG Cervera and  FP Torres. 2007 Soil properties and crop yields after 21 years of direct drilling trials in southern Spain. Soil Till Res 94: 47-54.Fengyun Z, W Pute, Z Xining and C Xuefeng. 2011. The effects of no-tillage practice on soil physical properties. Afr J Biotech 10: 17645-17650. Havlin, JL, JD Beaton, SM Tisdale and WL Nelson. 2005. Soil Fertility and Fertilizer: an Introduction to Nutrient Management. Pearson Prantice Hall. Sevent Edition. Upper Saddle River, New Jersey, 515 p.Karlen DL, NC Wollenhaupt, DC Erbach,  EC Berry, JB Swan, NS Eash and JL Jordahl. 1994. Crop  residue effects on soil quality following 10-years of no-till corn. Soil Till Res 31: 149-167.Kumar  A and DS Yadav. 2005. Effect of zero and minimum tillage in conjunction with nitrogen management in wheat (Triticum aestivum ) after rice (Oryza sativa.). Indian J Agron 50 (1): 54-57.Lal R. 1989. Conservation tillage for sustainable agriculture: tropics versus temperate environment. Adv Agron 42: 85-197.Lal R. 1997. Residue management, conservation tillage and soil restoration for mitigating greenhouse effect by CO2 enrichment. Soil Till Res 43: 81-107.Lal R. 2007.  Soil science in a changing climate. CSA New 52: 1-9.Mallory J J, RH  Mohtar, GC Heathman, DG Schulze and E Braudeau. 2011. Evaluating the effect of tillage on soil structural properties using the pedostructure concept. Geoderma 163: 141-149. doi:10.1016/ j.geoderma. 2011.01.018. 9p.Paustian K,  HP Collins and EA Paul. 1997. Management control on soil carbon. In: EA Paul, ET Elliot, K Paustian and CV Cole  (eds). Soil Organic Matter in Temperate Agro-ecosystems: Long-term Experiment in North America. CRC Press, pp. 15-50.Rasmussen, KJ. 1999. Impact of ploughless soil tillage on yield and soil quality: A Scandinavian review. Soil Till Res 53: 3-14.Quintero M. 2009. Effects of conservation tillage in soil carbon sequestration and net revenues of potato-based rotations in the Colombian Andes. [Thesis], University of Florida, USA. SAS [Statistical Analysis System] Institute. 2003. The SAS system for windows. Release 9.1. SASInst Inc, Cary, NC.Singh A and J Kaur. 2012. Impact of conservation tillage on soil properties in rice-wheat cropping system. Agric Sci Res J 2: 30-41.Six, J, SD Frey, RK Thiet and KM Batten. 2006. Bacterial and fungal contributions to carbon sequestration in agroecosystems. Soil Sci Soc Am J 70: 555-569.Smith JL and HP Collins. 2007. Management of organisms and their processes in soils. In: EA Paul (ed). Soil Microbiology, Ecology and Biochemistry. Third Edition. Academic Press, Burlington, USA, 532 p.Stockfisch N, T  Forstreuter, W Ehlers. 1999. Ploughing effects on soil organic matter after twenty years of conservation tillage in Lower Saxony, Germany. Soil Till Res 52: 91-101.Tarkalson, DD, GW Hergertb and KG Cassmanc. 2006. Long-term effects of tillage on soil chemical properties and grain yields of a dryland winter wheat-sorghum/corn-fallow  rotation in the great plains. Agron J 26: 26-33.                Thomas GA, RC Dalal, J Standley. 2007. No-till effect on organic matter, pH, cation exchange  capacity and nutrient distribution in a Luvisol in the semi-arid subtropics. Soil Till Res 94: 295-304.Utomo M, H Suprapto and Sunyoto. 1989. Influence of tillage and nitrogen fertilization on soil nitrogen, decomposition of alang-alang (Imperata cylindrica) and corn production of alang-alang land.  In: J van der Heide (ed.). Nutrient management for food crop production in  tropical farming systems. Institute for Soil Fertility (IB), pp. 367-373.Utomo M. 2004. Olah tanah konservasi untuk budidaya jagung berkelanjutan. Prosiding Seminar Nasional IX Budidaya Pertanian Olah Tanah Konservasi. Gorontalo, 6-7 Oktober, 2004, pp. 18-35 (in Indonesian).Utomo M,  A Niswati, Dermiyati, M R Wati, AF Raguan and S Syarif. 2010. Earthworm and soil carbon sequestration after twenty one years of continuous no-tillage corn-legume rotation in Indonesia. JIFS  7: 51-58.Utomo M, H Buchari, IS Banuwa, LK Fernando and R Saleh. 2012. Carbon storage and carbon dioxide emission as influenced by long-term conservation tillage and nitrogen fertilization in corn-soybean rotation. J Trop Soil 17: 75-84.Wang W,  RC Dalal and PW Moody. 2001. Evaluation of the microwave irradiation method for measuring soil microbial biomass. Soil Sci  Soc Am J 65: 1696-1703.Wright AL and FM Hons.  2004. Soil aggregation and carbon and nitrogen storage under soybean cropping sequences. Soil Sci Soc Am J 68: 507-513. Zibilske LM, JM Bradford and JR Smart. 2002. Conservation tillage induced change in organic carbon, total nitrogen and available phosphorus in a semi-arid alkaline subtropical soil. Soil Till Res 66: 153-163.